Capital equipment purchasing : optimizing the total cost of capEx sourcing - Hofmann, Erik (Professional supply management, 2012)
Capital equipment purchasing can significantly influence companies' economic success. However, in many companies the degree of professionalism of this particular form of procurement has not yet reached the required level. Likewise, from a scientific perspective, the topic leads more of a "shadowy existence". Compared to other main groups of procurement, capital equipment features numerous characteristics that significantly impact the purchasing process. The process of purchasing capital equipment therefore requires specific attention and above all a systematic approach. Due to these features, numerous challenges arise within the scope of capital equipment purchasing. To overcome these challenges, a holistic process model and specific tools and methods for capital equipment purchasing are presented. The following topics regarding capital equipment purchasing are presented: •             Compliance management •             Savings measurement •             Life cycle costs and total cost of ownership •             Determining the optimum useful life and replacement time •             Real options approach for the evaluation of investment alternatives •             Performance contracting Readers are provided with a comprehensive and structured process model for capital equipment purchasing. The comprehensive set of methods including various instruments and methods presented in this book support the establishment of a professional capital equipment purchasing process.